Bilateral Renal Lymphoma Detected by F-18 FDG PET/CT scan: A Case Report (Bangladesh Journal of Nuclear Medicine, 2024)
Diffuse large B-cell lymphoma (DLBCL) is the commonest subtype of non-Hodgkin’s lymphoma (NHL) and constitutes 25% of all NHL cases. Extranodal involvement includes the gastrointestinal, head and neck, orbital, central and peripheral nerve systems, thorax, bone, skin, breast, testis, thyroid, and genitourinary systems in 25-40% of HL patients, particularly NHL patients. Renal involvement in lymphoma is commonly seen in cases of widespread nodal or extranodal lymphoma, which is known as secondary renal lymphoma (SRL). This reported case of SRL was a known DLBCL patient. A young woman of 19 years diagnosed with DLBCL visited the PET-CT division of National Institute of Nuclear Medicine & Allied Sciences (NINMAS) for a18F-FDG PET-CT study to assess therapeutic response, metabolic characterization and staging. Post-chemotherapy abdominal CT and ultrasound were normal. However, 18F-FDG PET-CT revealed metabolically active lymphoma involving cervical, mediastinal, and abdominal lymph nodes, but unusual bilateral renal involvement modified the therapeutic management eventually.Bangladesh J. Nuclear Med. 26(2): 229-232, 2023